2015
DOI: 10.1007/s11368-015-1218-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of CaCl2-extractable heavy metals, polychlorinated biphenyls, and microbial communities to biochar amendment in naturally contaminated soils

Abstract: Purpose Biochar can be used to reduce the bioavailability and leachability of heavy metals, as well as organic pollutants in soils through adsorption and other physicochemical reactions. The objective of the study was to determine the response of microbial communities to biochar amendment and its influence on heavy metal mobility and PCBs (PCB52, 44, 101, 149, 118, 153, 138, 180, 170, and 194) concentration in application of biochar as soil amendment. Materials and methods A pot (macrocosm) incubation experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Additionally, the reduction of available forms of Cd and Pb reported in our study was beneficial for dehydrogenases activity. The results presented by Liu et al (2016) showed that these elements may be among the main inhibitors of dehydrogenases activity, and the decrease in soil pH changes the degree of oxidation of these metals and reduces their adverse effects on the enzymatic activity of soil. Studies of Zheng et al (2015) have found that only biochar produced from rice straw reduced the availability of Pb, but it was not reflected in the rice biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the reduction of available forms of Cd and Pb reported in our study was beneficial for dehydrogenases activity. The results presented by Liu et al (2016) showed that these elements may be among the main inhibitors of dehydrogenases activity, and the decrease in soil pH changes the degree of oxidation of these metals and reduces their adverse effects on the enzymatic activity of soil. Studies of Zheng et al (2015) have found that only biochar produced from rice straw reduced the availability of Pb, but it was not reflected in the rice biomass.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, it can be seen from results of the six immobilisation remediation experiments that the suitable conditions for immobilisation by Fe 3 O 4 @C-COOH in lead-contaminated soil are: AA of 3.3%, pH of 7.33, WC of 50%, conductivity of 142.6 μS•cm -1 , OM of 63.04 g•kg -1 , and an exposure time of no less than 10 days. However, Pb state could be transferred reciprocally and the transformation impacts the toxicity of heavy metal ions in soil [15,[43][44]. Therefore, a leaching toxicity test (TCLP) is an appropriate method to evaluate the stabilization treatment of heavy metal-contaminated soil [8].…”
Section: Fe 3 O 4 @C-cooh Ie By Tclp Test Methodsmentioning
confidence: 99%
“…Amending HM contaminated soils with biochar has shown increased microbial abundance which suggests increased HMs tolerance (Liu et al 2016, Chen et al 2017, with changes in microbial population size, composition and activity (Liu et al 2016, Yang et al 2016, Chen et al 2017, Xu et al 2018. A number of studies have shown biochar dosage influences soil microbial population and activity, at low concentrations of biochar (1%) increased the relative abundance of bacterial and fungal species, while at higher application rates (5%) abundance declined (Huang et al 2017).…”
Section: Soil Biologymentioning
confidence: 99%